2000
DOI: 10.1023/a:1008939328060
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Development of the ITG-ASF was a data-driven process maximizing measurement precision and breadth while minimizing burden. The ITG-ASF is a brief, comprehensive and empirically valid tool that complements traditional markers of the outcomes of asthma care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…15 This measure has been shown to have good cross-sectional construct validity and reproducibility 16,27 and to predict asthma severity, work days missed and to be responsive to changes in pulmonary function. 8 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 This measure has been shown to have good cross-sectional construct validity and reproducibility 16,27 and to predict asthma severity, work days missed and to be responsive to changes in pulmonary function. 8 …”
Section: Methodsmentioning
confidence: 99%
“…We expected the impact of asthma on QoL would be greater in persons with indicators of more uncontrolled asthma and more work days missed 8 and in persons with greater health care utilization (more emergency room visits and hospitalizations for asthma during the past year and more frequent use of controller medications).…”
Section: Methodsmentioning
confidence: 99%
“…3 It has been used in a number of studies over the years within and outside the United States. 3,5,2029 …”
Section: Methodsmentioning
confidence: 99%
“…The US review identified 9 instruments for adults, the ABP [14], the Asthma Impact Survey [15], the AQLQ-J-s [11], the mini AQLQ-J [12], the LWAQ [16], the modified AQLQ-S [17], the Asthma Short Form [18], the SGRQ [6,7] and the AQ-20 [17]. …”
Section: Introductionmentioning
confidence: 99%